Food security, freer agricultural trade and endogenous policy formation - Othman, Jamal (Universiti Utara Malaysia, 2003)
In light of the on going policy debate on globalization issues, this paper illustrates the implication of interest group influence and national strategic interests on policy formation in the Malaysian rice sub-sector when the policymaker welfare criterion was used in drawing up policies. This paper suggests a domestic and international political-economic scenario where joint welfare maximization will be the desirable policy choice among trading countries.